Parental homework-help profiles throughout grades 6 – 9: Relations to motivation and mathematics skills - Kikas, Eve; Mädamürk, Kaja; Silinskas, Gintautas (Frontiers in Education, 2022)
This study aimed to examine how parental profiles during homework help (supportive versus controlling) for children in Grades 6 and 9 change over time and relate to children’s motivation and math skills. Participants included 719 mother–child dyads. Children’s perceptions of parental help and math skills were assessed in both grades; children’s math-related self-concept, interest, and mother-rated task persistence were assessed only in Grade 6. Three similar profiles of parental help appeared in both grades. Most mothers and children belonged to the Average support and control profile (around 60% in both grades); 29–33% belonged to the Average support, high control profile; and 8–11% belonged to the Low support, below average control profile. Profiles differed based on children’s self-concept, task persistence, and math skills in Grade 6. Transitions of parental homework help predicted children’s math skills in Grade 9. These findings help to conceptualize parental homework help as a multidimensional construct that may manifest in three different profiles which differentially relate to the child’s skills and motivation.